The Analysis Methodics of Prediction Distress Using Financial Statements Information - Mackevičius, Jonas; Poškaitė, Dalia (Ekonomika, 1999)
The purpose of article - to overview methodics of analysis of prediction the financial distress of enterprise using financial statements and other information which play an important role in distress prediction.In the article there are suggested following methodics of analysis:1) evaluation items of financial statements2) using of financial ratios3) analysis of relations liquidity and profitability.The effectiveness of this methodics was practically evaluated by using indicators of the Lithuanian diary enterprises 1995-1999.